Out - Smolens, John (Book collections on Project MUSE., 2019)
"In the novel Out, a sequel to John Smolens's internationally-acclaimed Cold, Del Maki's house provides shelter for a group of characters whose lives are as volatile and unpredictable as the blizzard that lashes Michigan's north woods"--